Wiec poselski z udziałem posła S.D. Kol. Eugeniusza Czechowicza. (Malbork : [s.n.], 1951)
Afisz inf. o wiecu 28.10.1951 r.
Keywords: Czechowicz, Eugeniusz -- (1904-1964).; Stronnictwo Demokratyczne -- 1945-1970 -- druki ulotne; Malbork (Polska) -- 1945-1970 -- druki ulotne; Malbork (Polska) -- 1945-1970 -- źródła